Influence of different organic manures on the growth and yield of marigold (Tagetes erecta L.) plants (Journal of Biodiversity Conservation and Bioresource Management, 2023)
A pot experiment was conducted during rabi season in the year 2021-22 under net house condition of the Department of Soil, Water and Environment, University of Dhaka to evaluate the influence of different organic manures on the growth and yield contributing the characteristics of marigold. Seven types of organic manures, viz. Alo, Supermill, Mazim, Vermicompost, ACI, Kazi and Poultry manures were applied singly at the rate of 5 ton ha-1. The tallest plant of marigold (60 cm) found with Supermill, the maximum leaf number (367 plant-1) with Poultry manure, leaf area (6.56 cm2 plant-1), leaf area index (0.017), total fresh weight (15.55 g plant-1) and total dry weight (4.78 g plant-1) of marigold plants were recorded with Mazim organic manure.  The highest number of branches (78 plant-1), flowers (11 plant-1), diameter (2.80 cm), fresh weight (1.90 g plant-1) and dry weight (0.54 g plant-1) were recorded in ACI organic manure. The upper limit length (8.0 cm) of root and the length of shoot (51.30 cm) were recorded in Supermill. The highest root-shoot ratio (0.22) was recorded in Kazi organic manure. The standard range of number of flower’s was 6 to 11 plant-1 with the treatments without using synthetic fertilizer or any toxic pest control substance. The maximum number of flower (11 plant-1) obtained with ACI. The findings indicated the clear possibilities of growing safe and environment friendly marigold flower in context of Bangladesh. The study revealed that all the sources of organic materials enhanced the growth and yield component of marigold. The study also generated a new information as guide line for future research target. The organic sources may be arranged according to the production of number of marigold flower: ACI>Poultry litter> Mazim>Supermill >Alo>Kazi. Further investigation is needed for future research interest.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 39-48